Workshop on Sustainable Urban Development for Future Planner in Banjarmasin - Hanny Maria Caesarina; Hans Hasselt; Dienny Redha Rahmani; Maulidah Maulidah; Muhammad Faqih Tamami (Comment: an International Journal of Community Development, 2020)
Sustainable Urban Development is common in European countries, especially the Netherlands. Cities in the Netherlands already implemented some of the sustainability principles. This condition might differ from Banjarmasin which at the moment facing some urban problems such as water and water management, limited green space, etc. There is a similarity between cities in the Netherlands and Banjarmasin where the city has so many canals across the urban area. This community service intended for the students as future planner to acknowledge sustainable urban development and Sustainable Development Goals (SDGs). The students shall be able to apply the principles in the field after the workshop. The participants are the students of Urban and Regional Planning in University of Muhammadiyah Banjarmasin as the future planners. The tools and materials used along the training were Skype, Microsoft Power Point. The outcomes of this activity are the future planners can identify and analyze points of SDGs related to urban planning, and proposed ideas about the implementation of sustainable urban development in Banjarmasin.